Study of the effect of different curing setups on mechanical properties of low cost composite structures - Syed Muhammad, Kashif; Shaik Dawood, Mohd. Sultan Ibrahim; Abdur Razzak, M.; Azram, Mohammad; , (2013)
Laminated composite structures are frequently used in various engineering applications including aerospace, marine, and automotive structures. In the present work, effect of three different curing setups is studied onto the mechanical performance of E-glass/Epoxy composite plates fabricated by hand lay-up. Typical applications of such manufacturing methods are low cost composite structures for secondary or non load bearing applications. Through this experimental study, comparative analysis has been performed when composites plates are manufactured by three different curing set ups; conventional air cured (AC), air cured under press (PC) and vacuum bag cured (VC). It was observed that the plate properties were influenced with respect to the curing setup used. This study helps in classification of the studied three curing methods via-a-viz mechanical performance. Based on observed mechanical performance of the plates fabricated by the three different setups, vacuum bagging exhibited better results.